Market-led Agricultural Extension Challenges & Future Strategy - M.N.Reddy, (Journal of Agricultural Extension Management, 2025)
Indian agriculture has made rapid progress / strides in the last half century by augmenting the annual food grain production from 51 million tonnes in the early fifties to 209 million tonnes in 1999-2000 and steered the country to a status of self sufficiency. It has been successful in keeping pace with the rising food demand of a growing population. Food grain production quadrupled in the last 50 years while population nearly tripled from 350 million to one billion during this period. Significantly, the extension system had played its role untiringly in transfer of production technologies from lab to land besides the agricultural scientists, farmers and marketing network